LAKER SEBAGAI MEDIA SENI APLIKATIF KHAS PALEMBANG - Yosef Yulius (Besaung : Jurnal Seni Desain dan Budaya, 2016)
As one of the art and cultural heritages of the archipelago, Palembang’s lacquer put its position as a creative media for artists to work. With all the advantages and uniqueness, palembang’s lacquer still survive and exist from time to time to be recognized and studied as a science of art. As a natural creative media, Palembang’s lacquer is an alternative for the artists or designers from various branches of scientific art to try and apply the new skill and creativity in creating a work. With the presence of Palembang’s lacquer knowledge, the knowledge of the working process becomes more extensive and innovative, Palembang’s lacquer inspires the working process of artists or designers to be able to explore ideas or creative concept in the process of working more competently, in addition to all the advantages of Palembang’s lacquer, working with this media is expected to be able to bring and introduce the local culture of the archipelago to all the art lovers in Indonesia. Key words : The Traditional Furniture from Palembang, Aesthetic Values, Art Development, Product Designs, Lacquer, Art